2022
DOI: 10.2147/dmso.s330323
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and Exosomal microRNAs May Be Possible Targets to Investigate in Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus (GDM) is defined as glucose intolerance that occurs during the second or third trimester of pregnancy. As the incidence of GDM rises, so does the risk of maternal and fetal complications with short- and long-term consequences. As a result, early diagnosis and treatment of this condition are important to avoiding adverse pregnancy outcomes. Exosomes are tiny vesicles secreted by living cells which contain a variety of bioactive substances. They are released by cells to facilitate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…MicroRNAs (miRNAs) are a class of endogenous, non-coding, single-stranded RNAs with a length of approximately 22 nucleotides that regulate many cell processes ( 18 ). A large amount of evidence has indicated that exosomal lncRNAs and circRNAs could act as competing endogenous RNA (ceRNA) molecules or efficient miRNA sponges to regulate miRNA-targeted gene expression, transcription, and protein synthesis ( 19 , 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of endogenous, non-coding, single-stranded RNAs with a length of approximately 22 nucleotides that regulate many cell processes ( 18 ). A large amount of evidence has indicated that exosomal lncRNAs and circRNAs could act as competing endogenous RNA (ceRNA) molecules or efficient miRNA sponges to regulate miRNA-targeted gene expression, transcription, and protein synthesis ( 19 , 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…MicroRNAs, or miRNAs, are small, non-coding RNAs that interfere with mRNA translation to alter the expression levels of gene products ( 13 , 14 ). Current biomarkers for GDM do not provide early detection of who is at greatest risk, do not characterize differences in the specific risk profile, and do not always predict resulting complications ( 15 , 16 ). Circulating miRNAs are promising diagnostic biomarkers that represent environmental or behavioral influences on gene expression, potentially providing a more comprehensive measure of risk ( 15 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Exosomal microRNA (ExomiR) are 21-25 nucleotide long ( 12 ) nano-sized, non-coding RNA molecules serving pivotal regulatory roles in the progression of various diseases including insulin resistance in pregnant women. These ExomiRs can act as biomedical tools for a better prognosis of GDM and other pregnancy-associated complications like preeclampsia, preterm births, neonatal sepsis, etc ( 13 ). These molecules not only regulate but also act as significant biomarkers for several diseases, thereby helping to better diagnose the diseases.…”
Section: Introductionmentioning
confidence: 99%